Protocol for generating splice isoform-specific mouse mutants using CRISPR-Cas9 and a minigene splicing reporter - Yudong Teng; Kelsey Arbogast; Harald Junge; Zhe Chen (STAR Protocols)
Summary: Here, we present a protocol to alter the production of alternatively spliced mRNA variants, without affecting the overall gene expression, through CRISPR-Cas9-engineered genomic mutations in mice. We describe steps for designing guide RNA to direct Cas9 endonuclease to consensus splice sites, producing transgenic mice through pronuclear injection, and screening for desired mutations in cultured mammalian cells using a minigene splicing reporter. Splice isoform-specific mouse mutants provide valuable tools for genetic analyses beyond loss-of-function and transgenic alleles.For complete details on the use and execution of this protocol, please refer to Dailey-Krempel et al.1 and Johnson et al.2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.